WHAT IS AN ORAL HEROIC EPIC POETRY? – OVERCOMING THE LIMIT OF THE ILIAD - PARK, Jong-Seong (International Journal of Korean Humanities and Social Sciences, 2020)
The ancient Greek epic Iliad, including the oral epic and the written epic, has enjoyed a solid status as a ‘heroic epic’ (or ‘narrative poetry’) of European literature. But if a reader takes look at the general aspects of the heroic epic of oral tradition, it turns out that Iliad is not a typical work of a typical epic, but rather an individual one. Because the birth, trials, performance, and ending of a hero’s life are divided relatively evenly, and the general pattern of transferring the hero’s life to the heroic epic of oral tradition can be found in such cases as Manas, Jangar, Gesar and Mwindo.